The Revolution of Small Snails and the Early Modern Evolutionary Fauna - Stefano Dominici (Diversity)
The species richness of major clades and functional groups among gastropods, a key element of Modern Evolutionary Fauna (MEF), underlines the dominant role of carnivorous Caenogastropoda and Heterobranchia, including small ectoparasites and micrograzers, at modern tropical latitudes. Neogastropoda are active predators that radiated in the Cretaceous, but their early Mesozoic MEF roots are poorly understood. The escalation hypothesis emphasises prey–predator interactions as gastropods’ macroevolutionary drivers during the Mesozoic Marine Revolution but overlooks the significance of highly diversified smaller forms. The tropical fossil record of the Permian–Triassic mass extinction (PTME) and the Triassic rise of MEF suggests that non-carnivorous species dominated gastropod fauna immediately before and after the PTME: Permian micrograzers mainly fed on sponges and waned during the rise of MEF, while ectoparasites and micrograzing carnivores diversified starting from the Ladinian period. Patterns of gastropod species richness, size, and form, the fossil record of reef builders and other benthic invertebrates, and an analysis of stem neogastropods jointly suggest a Middle Triassic revolution of small-sized gastropods, triggered by the emergence of scleractinian corals and the diversification of echinoderms. Habitat heterogeneity and new food sources offered niches for the early radiation of modern gastropod clades.